Cystic Fibrosis of the Pancreas: The Role of CFTR Channel in the Regulation of Intracellular Ca2+ Signaling and Mitochondrial Function in the Exocrine Pancreas - Madácsy, Tamara; Pallagi, Petra; Maleth, Jozsef (Frontiers in Physiology, 2018)
Cystic fibrosis is the most common genetic disorder that cause a significant damage in secretory epithelial cells due to impaired ion secretion by the cystic fibrosis tarnsmembrane conductance regulator (CFTR) Cl- channel. The organs most frequently damaged by the disease are the lung and the pancreas. The damage of the exocrine pancreas leads to pancreatic insufficiency, abdominal pain and an increased risk of acute pancreatitis in cystic fibrosis patients causing significant decrease in the quality of life. Therefore the understanding of the role of CFTR in the ductal secretory functions is highly interesting. However, several recent study indicated that CFTR has a central role in the intracellular signalling processes and is now considered as a signalling hub in epithelial cells. In addition, impaired CFTR expression has been connected with sustained elevation of the intracellular Ca2+ and with damaged mitochondrial function in epithelial cells. These observations are obscured in the exocrine pancreas, although very similar intracellular changes were described in acute pancreatitis. Therefore in this review we would like to summerize the complex role of CFTR in the exocrine pancreas with a special focus on the intracellar signalling and mitochondrial function.